Transnational Cervantes - Childers, William (University of Toronto romance series., 2006)
Theoretically eclectic and methodologically innovative, Transnational Cervantes opens up many avenues for research and debate, aiming to bring Cervantes' writings forward into the brave new world of our postcolonial age.